Some developmemt and improvement of ED XRF tecniques in Mongolia - Sh, Gerbish; J, Bayarmaa (Scientific transaction of the National University of Mongolia. Physics, 2022)
The Nuclear Research Center, National University of Mongolia, Ulaanbaatar has got three ED XRF systems with isotope sources (Fe-55, Cd-109, Am-241, Co-57) from 1976, secondary target from 1981 and total reflection X-ray techniques from 1993. This facility is used for training, research and analytical services.